What Were They Thinking?! Students’ Decision Making in L1 and L2 Translation Processes - Pavlović, Nataša (HERMES - Journal of Language and Communication in Business, 2010)
In spite of the ‘Golden Rule’ that translators should only work into their ﬁrst language, translation into the second language (L2 translation) is a fact of life in settings involving languages of ‘limited diffusion’. Even in countries that use one of the traditionally ‘major’ languages, research into L2 translation and its training is becoming increasingly topical with the emergence of global translation markets and the worldwide dominance of English. This paper examines novice translators’ decision-making in video- and audio-recorded collaborative (group) translation processes in two directions: into the students’ ﬁrst language (Croatian) and from that language into their second language (English). The study aims to identify and classify the different arguments the subjects use in deciding which of the tentative solutions to translation problems to use in the ﬁnal version of their translation. It is hypothesised that similar arguments are used in both directions but with a different distribution. Only the former hypothesis is fully corroborated by the evidence from the verbal protocols.